Overexpression of the Fork Protection Complex: a strategy to tolerate oncogene-induced replication stress in cancer cells. (4th July 2019) - Pasero, Philippe; Tourrière, Hélène
ABSTRACT: Oncogene-induced replication stress (RS) plays an active role in tumorigenesis by promoting genomic instability but is also a challenge for cell proliferation. Recent evidence indicates that different types of cancer cells adapt to RS by overexpressing components of the ATR-CHK1 pathway that promote fork progression in a checkpoint-independent manner.